Histórias de silêncio para encenar romance-peça - Centenaro, Natasha (2014)
The present master s degree dissertation is inserted in the concentration area of Creative Writing, is constituted of a literary text, a fictional work, and a text of theoretical-reflexive nature. The literary text is a novel-play entitled Histórias de silêncio para encenar. As a work of hybrid genre, it aims to connect fiction as prose - the novel, with the dramatic text; this way the scenes from the play are juxtaposed to the chapters of the novel, as part of the same narrative structure. The plot of the novel-play is about a theater group formed by five components (the director and writer, two actresses and two actors) in a collaborative process of creating and assembling the play. Throughout this elaboration time and during rehearsals the internal and external relations of the group develop, such as situations and conflicts (family, social, psychological and professional) that conduct the novel. The theoretical-reflexive text complements the fictional one in the form of a Postface, with the objective of raising the debate about hybrid genres in literature, started in the proposal of the novel-play. The Postface also presents a reflection on the creative process, the difficulties, the influences and inspirations in the confection of the literary work. However, it does not intend to be and interpretative analysis or a guide to reading the novel-play, it points to reflections that rose in the writing of it. At the end, annexed is the material that composed the work as part of its genetic dossier.